Economic Policies and Elections. A principal-agent point of view - António Caleiro (Universidade de Évora, Departamento de Economia, 2004)
One of the most crucial lessons to be taken from the literature on electoral business cycles is that the short- run electorally-induced fluctuations prejudice the long-run welfare. Since the very first studies on the matter, some authors offered suggestions as to what should be done against this electorally-induced instability. The problem assumes an interesting form, given that we can presume that if electoral business cycles do exist it is because voters, being ignorant, allow them to exist or, indeed, because the government, in the case of implementing policies that are optimal in the long-run for society, may be electorally punished by voters. As the government's optimal policies depend crucially on the behaviour of voters, the paper analyses the circumstances under which a non-representative behaviour of voters may induce the government to behave as representative of the society's interests (without punishing it). As is well-known, governments may have the temptation to exploit the Phillips curve. This discretionary way of making economic policy generates an inflation bias. The literature has then evolved to analyse possible punishment strategies in order to avoid that discretionary behaviour. Traditionally it is considered that the punishment takes the form of people considering announced policies as non-credible. This introduces the problem of arranging the right mechanism or moment in time to implement these punishment strategies. It turns out that elections are indeed the appropriate mechanism to punish or to reward the past behaviour of the incumbent. In fact, elections can be used to turn voters, i.e. the public into the principal who has all the incentives to motivate the government, as the agent, to use the appropriate policies. The paper analyses the circumstances under which an optimal contract can be established between the electorate and the government in order to guarantee that the government behaves in accordance with the true interests of the society.
http://hdl.handle.net/10174/8415
Keywords: D72; E32; E61; 330; Economic Policies; Elections; Optimal Contracts; Principal-Agent